Composition of the editorial staff of major spinal journals based on geo-economic background: A survey analysis - Zhiwei Jia; Donghua Liu; Xingxuan Li; Tianlin Wen; Xiyan Zhao; Wei Li (Heliyon, 2024)
Background: The widespread absence of papers originating in low and middle income economies (LAMIE) across various scholarly disciplines has been widely acknowledged. One potential reason for this could be editorial biases against submissions from LAMIE. Although this bias has been observed in different academic areas, its extent in spinal research remains largely uninvestigated. This research endeavored to investigate the composition of editorial staff members (ESM) within major spinal journals and scrutinize the degree of international diversity represented among the ESM. Methods: We pinpointed ten major spinal journals by referencing their presence in the Journal Citation Reports of 2021. Countries of the ESM affiliated with these journals were categorized according to World Bank classifications. Following this, we conducted a thorough analysis of the ESM compositions. Results: A total of 982 ESM from 50 countries were identified. The United States exhibited the highest representation among ESM (395, 40.22%), followed by South Korea (57, 5.80%), Switzerland (53, 5.40%). When segmented by geographical regions, North America emerged with the highest representation, constituting 43.38% of ESM at 426, trailed by Europe & Central Asia at 31.16% (306), East Asia & Pacific at 17.92% (175). The majority of ESM, amounting to 87.98%, hailed from high income economies (HIE). There was an absence of ESM representation of low income economies. The relationship regarding the quantity of ESM in each country and its population failed to demonstrate significance (p = 0.274, r = 0.281). However, a notable positive correlation emerged when exploring the connection between ESM numbers and gross domestic product (p = 0.033, r = 0.517). Conclusions: Major spinal journals exhibit a notable absence of international representation within their editorial boards, predominantly comprising members from HIE. This underscores a substantial underrepresentation of ESM originating from LAMIE within the sphere of spinal investigation.